Outcomes of Admissions for Preterm Labor - Michael W. Kuzniewicz; Libby Black; Eileen M. Walsh; Sherian X. Li; Mara Greenberg (Thieme Medical Publishers, Inc., 2017)
Abstract Objective This study aims to quantitate the incidence of preterm labor (PTL) admissions and determine the frequency and predictors of preterm delivery (PTD) during these admissions. Study Design Retrospective cohort of singleton pregnancies within Kaiser Permanente Northern California, 2001 to 2011. PTL admissions were defined as inpatient encounters > 24 hours with an International Classification of Diseases, 9th Revision code for PTL. Results Total study population was 365,897 with PTL admission rate 11%. PTD occurred in 85% of pregnancies with PTL admission. Delivery occurred within 48 hours of admission in 96% ≥34 weeks, 67% 31 to 33 weeks, and 51.9% <31 weeks. Predictors of delivery during PTL admission included gestational age 34 to 36 weeks (adjusted odds ratio [aOR], 6.90), chorioamnionitis (aOR, 105.58), and preterm rupture of membranes (aOR 19.29). Conclusion We demonstrate a high rate of PTD per PTL admission in a highly integrated health care system. More work is needed to determine optimal practices for hospitalization and treatment of women diagnosed with PTL.